2000
DOI: 10.1097/00000542-200002000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Does Not Alter Cardiac Function or Major Cation Currents in Isolated Guinea Pig Hearts or Myocytes

Abstract: Unlike hydrocarbon-based gaseous anesthetics, Xe does not significantly alter any measured electrical, mechanical, or metabolic factors, or the nitric oxide-dependent flow response in isolated hearts, at least partly because Xe does not alter the major cation currents as shown here for cardiac myocytes. The authors' results indicate that Xe, at approximately 1 MAC for humans, has no physiologically important effects on the guinea pig heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 0 publications
5
40
0
8
Order By: Relevance
“…The study of Nakayama et al in this issue of the Journal 1 is important because it convincingly supports this. The results are consistent with xenon's lack of action on some important cardiac ion channels, 11,12 and also with its lack of hemodynamic depression in healthy humans, 13 in patients with ischemic heart disease, 14 and in dogs with normal hearts and with cardiomyopathy. 15 Furthermore, xenon produces analgesia 10,16 and thereby suppresses hemodynamic and catecholamine responses to surgical stimulation, 17,18 further contributing to hemodynamic stability.…”
Section: Clinical Advantages Of Xenonsupporting
confidence: 73%
See 1 more Smart Citation
“…The study of Nakayama et al in this issue of the Journal 1 is important because it convincingly supports this. The results are consistent with xenon's lack of action on some important cardiac ion channels, 11,12 and also with its lack of hemodynamic depression in healthy humans, 13 in patients with ischemic heart disease, 14 and in dogs with normal hearts and with cardiomyopathy. 15 Furthermore, xenon produces analgesia 10,16 and thereby suppresses hemodynamic and catecholamine responses to surgical stimulation, 17,18 further contributing to hemodynamic stability.…”
Section: Clinical Advantages Of Xenonsupporting
confidence: 73%
“…publiée dans le présent numéro 1 est importante, car elle vient appuyer cette affirmation de façon convaincante. Les résultats cadrent avec l'absence d'action du xénon sur d'importants canaux ioniques cardiaques, 11,12 et aussi avec l'absence de dépression hémodynamique chez des sujets en bonne santé 13 ou qui présentent une cardiopathie ischémique 14 et chez des chiens dont le coeur est normal ou qui sont atteints de cardiomyopathie. 15 De plus, le xénon produit de l'analgésie 10,16 et, donc, supprime les réponses hémo-dynamiques et de la catécholamine à la stimulation chirurgicale, 17,18 contribuant davantage à la stabilité hémodynamique.…”
Section: Les Avantages Cliniques Du Xénonunclassified
“…It has been suggested that the underlying mechanism is the slight or nonexistent electrophysiological action of xenon on the important cation channels, including sodium, L-type calcium, and inward-rectifier and outward voltage-gated potassium channels [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Contrariamente aos restantes anestésicos inalatórios, o xénon exerce poucos efeitos nos principais canais iónicos, incluindo os canais de sódio (I Na ) , cálcio (I Ca, L ) e potássio (I K,ir ) 22 em miócitos de porco estudados in vitro. 23 Também em preparações de miocárdio de suínos, foi constatado que o xénon não interfere na condução auriculoventricular. 24 Sendo de frisar o facto de o xénon, em contraste com os restantes anestésicos voláteis, não afectar as respostas fisiológicas a estímulos ionotrópicos ou cronotrópicos positivos (ex: isoproterenol ou cálcio).…”
Section: Sistema Cardiovascularunclassified